Prevalence of Lewis Blood Group among Bangladeshi Population - Dipta, Tashmim Farhana; Rahman, Hafizur; Khatun, Ayesha; Islam, Md Ashadul (Anwer Khan Modern Medical College Journal, 2017)
Background: The Lewis system differs from all other blood group systems. It is primarily a system of soluble antigens originate in the tissue of body secretions, such as saliva (glycoprotein) and in plasma (glycolipid) respectively.The ABH secretor status influences red cells of Lewis phenotype and this phenotype may be modified by the ABO phenotype. Methodology: A cross sectional study was done to determine the presence of Lewis antigens in patients and voluntary donor's blood and observe the agglutination pattern during blood cross matching. In this study 350 blood samples were tested by hemagglutination -monoclonal antibodies. Result: Our study showed, Lewis antibody was detected in 50.8 % cases. The presence of anti-Leb was more frequent (69.7%) than anti-Lea in association with ABO blood group. Lewis anti-Leb was most common in O group (75.0%) followed by group-A (69.0%) where as anti-Lea was predominant in B (37.7%) followed by AB (33.3%).Moreover among Lewis phenotypes, Le (a-b+) was present in 35.4% cases, Le (a+ b-) in 15.1% and Le (a+ b+) was rare (0.3%). Phenotype Le (a-b-) represents all negative cases 172 in number (49.2%). Conclusion: Presence of Lewis antibody cause irregular agglutination interfering with interpretation of compatibility testing. So the patients with multiple transfusions or having atypical or irregular antibodies should routinely test for Lewis blood group antibodies to avoid untoward reactions. Anwer Khan Modern Medical College Journal Vol. 7, No. 2: Jul 2016, P 12-15